2012
DOI: 10.5897/ajar12.025
|View full text |Cite
|
Sign up to set email alerts
|

Sowing date and boll position affected boll weight, fiber quality and fiber physiological parameters in two cotton (Gossypium Hirsutum L.) cultivars

Abstract: To study the effects of sowing date and boll position on fiber quality and the physiological mechanism, field experiments were conducted using two cotton cultivars (Kemian 1 and Sumian 15) with two sowing dates (normal sowing date 25 April, and late sowing date 25 May) at Nanjing (118°50′E, 32°02′N), Jiangsu, China, in 2006 and 2007. Cotton bolls were divided into three parts (low, middle and upper) according to the fruiting branch symbodial positions. Boll weight, fiber quality (bundle strength, span lengths,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
7
1
0
Order By: Relevance
“…Buttar et al (2010) also reported that NM, sympods, and plant height could not vary significantly in different sowing environments. Zhao et al (2012) and Jamro et al (2017) also reported similar type of results. It showed that the performance and productivity of upland cotton can be higher when the crop is sown on or before the normal sowing time (before May 10).…”
Section: Discussionsupporting
confidence: 53%
“…Buttar et al (2010) also reported that NM, sympods, and plant height could not vary significantly in different sowing environments. Zhao et al (2012) and Jamro et al (2017) also reported similar type of results. It showed that the performance and productivity of upland cotton can be higher when the crop is sown on or before the normal sowing time (before May 10).…”
Section: Discussionsupporting
confidence: 53%
“…This might due to relatively low temperature of air and at the beginning of the season for early planting (Table 1), which directed the cotton plants to keep the balance between vegetative growth and fruiting capacity while, in late planting, the increase of air and soil temperature. Such findings are in harmony with those obtained by Hamed (2011), Ismail et al (2012, Wenqing et al (2012), Elayan et al (2013) and Elayan et al (2015).…”
Section: Discussionsupporting
confidence: 91%
“…Shorter plants are always having lower maintenance respiration than longer ones. The obtained results are in agreement with those recorded by Reddy et al (1999), El-Sayed (2005), Emara et al (2009) and Wenqing et al (2012) and in disagreement with Boquet et al ( 2003). The present data also show that the growth regulator PIX at 50 ppm followed by IAA 50 ppm exhibited high value and did not differ significantly in the mean performance of boll weight (2.58 ,2.65) and (2.44 ,2.55) in (2010 and 2011), respectively, while NAA at 30 ppm exhibited lower value of mean performance of boll weight.…”
Section: Boll Weightsupporting
confidence: 89%
“…This might be due to relatively low night temperature of early planting date at the beginning of the season which prolonged the period of the appearance of the first bud, flowering and bolling. Similar results were obtained by Emara et al (2006), Abd El-Twab ( 2009) and Wenqing et al (2012). Data also showed that the mean performance of PIX growth regulators at 50 ppm was superior in phenologyical stage which gave the best reading in all No.…”
Section: Days To First Bud Flower and Open Bollsupporting
confidence: 88%
See 1 more Smart Citation